2006
DOI: 10.1021/ja060519g
|View full text |Cite
|
Sign up to set email alerts
|

Allylcyanation of Alkynes:  Regio- and Stereoselective Access to Functionalized Di- or Trisubstituted Acrylonitriles

Abstract: Allyl cyanides are found to add across alkynes in the presence of a nickel catalyst prepared from Ni(cod)2 and P(4-CF3-C6H4)3 in situ to give variously functionalized di- or trisubstituted acrylonitriles in highly stereoselective manners possibly via a pi-allylnickel species as an intermediate. alpha-Siloxyallyl cyanides also react at the gamma-position of a cyano group with both internal and terminal alkynes having various functional groups to give silyl enol ethers, which give the corresponding aldehydes or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 12 publications
3
41
0
1
Order By: Relevance
“…An alkyl-CN bond, which is cleavable under nickel/LA catalysis, [5] is compatible (entry 10, Table 1). The observed regioselectivities were fair to excellent and identical to what had been observed for the carbocyanation reaction of alkynes with other nitriles; [5,7] the major product was always the isomer having the larger substituent at the cyano-substituted carbon.…”
Section: In Memory Of Makoto Kumadasupporting
confidence: 77%
“…An alkyl-CN bond, which is cleavable under nickel/LA catalysis, [5] is compatible (entry 10, Table 1). The observed regioselectivities were fair to excellent and identical to what had been observed for the carbocyanation reaction of alkynes with other nitriles; [5,7] the major product was always the isomer having the larger substituent at the cyano-substituted carbon.…”
Section: In Memory Of Makoto Kumadasupporting
confidence: 77%
“…In 2006, Hiyama et al disclosed a Ni/PMe 2 Ph catalyst, which was found to effect regio-selective addition of cyanoformate esters across allene, giving rise to 3-alkoxycarbonyl-3-butenenitriles (Scheme 23) (29). Functional groups such as cyano, protected hydroxyl, and amino groups in the allene substrates are tolerated with the isolated yields up to 84% under very mild reaction condition (50°C).…”
Section: Element-cn Bonds Activation Reactionsmentioning
confidence: 99%
“…α-Siloxyallyl cyanides also react at the γ -position of a cyano group with both internal and terminal alkynes to give silyl enol ethers, which can be converted into the corresponding aldehydes or ketones upon hydrolysis. 70 Nickel-catalysed coupling of enynes (46) with allyl chlorides has been reported to occur in the presence of zinc; the reaction gives rise to the cyclic products (47) in good yields. 71 …”
Section: Additions Initiated By Metals and Metal Ions As Electrophilesmentioning
confidence: 99%
“…(68)] and alkynones with organoboronic reagents. These reactions afford six-membered allylic alcohols (69) de and/or their five-membered counterparts (70), whose ratios are dramatically affected …”
Section: Additions Initiated By Metals and Metal Ions As Electrophilesmentioning
confidence: 99%